Forging towards quality education A case study of a Malaysia public University - Leong, Huey Yng (2004)
The era of globalisation has led to the changing landscape of higher education and it presents many challenges and opportunities to Malaysia. Malaysian higher education is undergoing a rapid transformation period parallel to higher education reforms in many countries in the world. The public universities have shifted their roles from nation building to producing K-workers to fulfil the vision 2020. As the country aspires to become the regional educational hub and a centre for educational excellence, the focus has moved towards quality education. This research is primarily a case study on University of Malaya (UM) that was once synonymous linked to the image of excellence, prestige, quality education and research. However, over the years it has lost its competitive advantage in the marketplace in the expanse of student enrolment expansion. With this realisation, UM has embarked on a journey of transformation to strive towards educational quality and to become world-class. This study explores on how UM can achieve the desired goal by using the strategic management framework. A strategic historical analysis was performed on UM to understand the historical development of its strategy, structure and decision-making. Five significant eras were identified namely the foundation era, the consolidation era, the restructuring era, the corporatisation era and the innovative era. UM’s ethos, its core value, its promise and its unique positioning is best represented by the Brand platform of UM reflecting its brand essence and integrated with its function, personality, differentiation and source of authority to provide the commanding stature of UM in the Malaysian HE. The ability to mobilise change and to effectuate the necessary steps to be taken depend on UM’s ability to scan and understand the environment within its operation, to evaluate its strengths, weaknesses, opportunities and threats, to identify the resource gaps and to benchmark in adopting the best practices and in building the organisational capabilities. The transformation of UM requires a well-planned and coherent strategy to transform UM to be effective, efficient and productive towards the attainment of its educational quality. Hence, a balanced scorecard was created for UM to translate its strategies into specific objectives and performance measures and the value chain of the University was identified. The transformation of UM involves the interaction and synergy of the organisational structure, management style, systems, skills and most importantly the staff who are committed to change and embrace the culture of quality and excellence and having the shared visions to raise the standards of UM to international standards.